Four-quadrant operations and control of a three-phase BLDC motor for an electric vehicle - Majhi, Sanoj; Bhattarai, Bhriguraj; Karna, Anitesh Kumar (Journal of Engineering and Sciences, 2025)
This project demonstrates the control of a brushless direct current (BLDC) motor in all four quadrants (forward/reverse motoring/braking) using a universal bridge. The output of the universal bridge is fed to drive the motor. During the motoring mode, buck operation through the universal bridge of the battery takes place, and during regenerative mode, the mechanical energy is converted into electrical energy and is stored in the same chargeable battery through the boost operation. This concept could be applied in an electric vehicle downhill run by controlling the speed in the gravitational action, where the speed becomes more than the reference speed. As the electric vehicle operates with frequent start/stop, the scheme proposes the recovery of energy for every stopping operation through regenerative braking. Also, when an electric vehicle (EV) is going downhill, the controlled speed provides energy return to the battery. MATLAB/Simulink software is used to verify the above operations.